Hidranencefalia e hipoplasia cerebelar congênita em búfalos Murrah - Fiss, Letícia (2009)
Hereditary hydrancephaly and cerebellar hypolasia are reported in Murrah buffalos. Six calves, one female and 5 male out of 128 born between 2004 and 2008 in a farm in southern Brazil were affected. All affected calves were offspring from the same bull. No affected buffaloes were observed in the descendants of other three bulls used in the farm. Main clinical signs were depression, blindness, difficulty or impossibility to standing up, wide-based stance, and intention tremors. There is mild doming of the skull. The brain was smaller than normal. The cerebral cortex was almost complete absent leaving only membranous sacs fluid filled. The gyri were absent or narrower than normal in the occipital cortex. On the cut of the telencephalic cortex cavities were observed in the subcortical white matter. Smaller bilateral and symmetric cavities, containing fluid (porencephaly), were also observed in the basal nuclei. The lateral ventricles were dilated (hydrocephalum ex-vacuo). The cerebellum was smaller than normal. The brain stem appears normal, except by a side reduction in relation with the brain of a control calf. Upon histologic examination, in all buffalos, cavities of the subcortical white matter were limited by normal nervous tissue. Within cavities, residues of white matter sometimes bordered by ependymal cells were observed. The cortex was thin. Gitter cells, axonal spheroids, and gliosis were occasionally observed. Cerebellar disorganization, characteristic of cerebellar hypoplasia, and hypomyelinogenesis were observed in the cerebellum. Imuno-histochemistry and serologic tests were negative for bovine virus diarrhea and blue tongue viruses. These results associated with epidemiologic data suggest that the disease is a hereditary hydrancephaly and cerebellar hypoplasia, probably transmitted by a recessive autossomic gen.